Home / Вакансии и резюме / Все / Архитектура и строительство / Упростите выражение а) (с-2)(с+3)-(с^2) б) 7(х+8)+(х+8)(х-8) в) (х+5)4х-((2х+5)^2)

Упростите выражение а) (с-2)(с+3)-(с^2) б) 7(х+8)+(х+8)(х-8) в) (х+5)4х-((2х+5)^2)

Упростите выражение
а) (с-2)(с+3)-(с^2)
б) 7(х+8)+(х+8)(х-8)
в) (х+5)4х-((2х+5)^2)

  • А) = c+3c-2c-6-c=c-6
    б) = 7x+8x+x-64=x+15x-64
    в) = 4x+20x-4x-20x-25=-25
  • 1.
    a) c-2c+3c-6-c=c-6
    б) 7x+56+x-64=x+7x-8
    в) 4x+20x-4x-20x-25= -25

    2.
    a) 8(x-y)=8(x-y)(x+y)
    б) -(a-6a+9)= — (a-3)
    в) ab(b-a)=ab(b-a)(b+a)

    3.
    x(x-2x+x-2)=x-x
    x-x-2x-x+x=0
    -2x=0
    x=0

    4.
    a) (3x-3y)+(xy-xy)=3(x-y)+xy(x-y)=(x-y)(3+xy)
    б) (a-2)(a+2a+4)

    5.
    4x-20xy+25y=(2x-5y)0 при любых значениях переменных.

About Author: